The Analysis Of Medical Records Confidentiality Protection In Compliance With The Clinical Accreditation Standard 3.4 At Klinik Prima Husada- Bandung - Lanao, Fatima; Aksan Halim, Prihartono (Publikasi Indonesia, 2023)
The purpose of this study is to analyse medical record confidentiality protection in compliance with the clinical accreditation standard 3.4 at Klinik Prima Husada. A quantitative research method with a descriptive approach was used. Data was collected through observations, questionnaires, and literature reviews. Based on the findings with the number of samples of n = 11 respondents other indicators performed significantly above chance, but not other indicators. After the analysis, we conclude that the confidentiality of medical records at Klinik Prima Husada has not fully complied with the confidentiality aspects of medical records in some terms